Implementasi Kesantunan Bahasa Tokoh Novel Megat Karya Rida K Liamsi - Syafrial, Syafrial; Rumadi, Hadi (GERAM, 2019)
The background of this research was to promote the application of politeness language as a form of substantial local wisdom in addition to enrich the literary vocabulary that was novel. The formulation of this problem was the objective of this research was to analyze novel character of language politeness Megat work Rida K Liamsi. Further, the benefits of this research that was practical and theoretical in term of contrubution. The basic theory of politeness language was used and the nature of the novel. This type of research was qualitative. The method used was descriptive analytic method. Data collection techniques was documentation and librarianship in analyzing the words, phrases, clauses, or sentences that express politeness language speaking. Technique of data analysis performed by reading to concluded the results. The results of this research were identified as many as 35 maksim wisdom; 14 conspiracy, 13 awards, 13 generosity, 4 simplicity, and 9 sympathy respectively.